Antioxidant and Cytotoxicity Studies of Nypa fruticans (Nypa Palm Sugar) Extract - Wan M. A. W. Sabri; Mohd R. Asaruddin R. Asaruddin; Ahmad H. Sukairi; Syed A. T. W. Yusop (Indonesian Journal of Pharmaceutical Science and Technology, 2018)
Nypa fruticans Wurmb which belongs to the family of Arecaceae is one of the most widely distributed and useful palm in the mangrove forests in the Southeast Asia. Nypa palm sugar or commonly known as “Gula Apong” was processed using nypa palm sap as raw material. The nypa palm sugar was expected to benefit wider community as source of alternative sweetener. In this study, 2, 2-diphenyl1-picryhydrazyl (DPPH) scavenging activity and cytotoxicity test of methanol extract of nypa palm sugar were conducted. The antioxidant activity was determined based on DPPH scavenging activity of extract. The cytotoxicity test was conducted against brine shrimp Artemia salina, and the LC50 value of the extract was calculated. The antioxidant activity showed that the EC50 of nypa palm sugar was 1304 mg/mL while the value of EC50 for ascorbic acid was 0.6112 mg/mL. The results of the cytotoxicity showed that the methanol extract of nypa palm sugar was interpreted as non-toxic as the value of LC50 was 184.0 mg/mL.Keywords: 2,2-diphenyl-1-picryhydrazyl, antioxidant, cytotoxicity, Nypa fruticans, nypa palm sugar